1121. Does Anti-Vaccine Equal Anti-Antibody? Differing Rates of Veteran Acceptance of Monoclonal Antibody Therapies for COVID-19 By Prior Vaccination Status. (15th December 2022) - Brennan, Martha; Shumaker, Amy Hirsch; Stiefel, Usha
Abstract: Background: We assessed correlation between prior acceptance of COVID-19 vaccination and acceptance of monoclonal antibody (MAb) treatment for mild-to-moderate COVID-19. Methods: Adult outpatients evaluated for treatment with MAb between August 31 st, 2021 and April 23, 2022 in a large tertiary care VA healthcare system were included. MAb therapies administered over the period included casirivimab-imdevimab, sotrovimab, and bebtelovimab. All patients were screened by a small central clinician team with experience discussing COVID therapies under Emergency Use Authorization (EUA). Baseline characteristics, rationale for not offering MAb, and rates of vaccination and acceptance of therapy were recorded. In addition, rates of acceptance for the initial 4 months were compared to rates during the second 4 months of the program, using Chi-square or Fisher's exact test. Results: 203 patients (mean age 68, 91% male) with early COVID-19 were screened for MAb. 68% were vaccinated. 158 (78%) of those screened were offered MAb. The most common reason MAb was not offered was duration of illness longer than specified by EUA (65%). 112 (71%) patients offered MAb accepted, and 94 (84%) received MAb. Of 106 vaccinated patients offered MAb, 81 (76%) accepted. In contrast, of 52 unvaccinated patients offered MAb, only 31 (60%) accepted (Chi-square p = 0.046). However, when analyzed over time, unvaccinated patients were significantly more likely to accept MAb during the second 4 months of the program (7/7 patients, 100%) than during the first 4 months of the program (24/45 patients, 53%, Fisher's exact p = 0.033). This disparity was not seen in vaccinated patients, who accepted MAb at a rate of 73% during the first half of the program, and 88% during the second half (Chi-square p = 0.19). Conclusion: Vaccinated patients were significantly more likely to accept MAb therapy for COVID-19 than unvaccinated patients, suggesting that willingness to accept COVID-19 vaccination predicts willingness to accept other COVID-19 therapeutics. However, disparity in acceptance rates in our population is significantly attenuating over time, suggesting a "late-adopter, " phenomenon that has implications for continued efforts to encourage therapeutics and vaccines for COVID-19. Disclosures: All Authors : No reported disclosures.